2001
DOI: 10.1074/jbc.m105154200
|View full text |Cite
|
Sign up to set email alerts
|

GTPγS Regulation of a 12-Transmembrane Guanylyl Cyclase Is Retained after Mutation to an Adenylyl Cyclase

Abstract: DdGCA is a Dictyostelium guanylyl cyclase with a topology typical for mammalian adenylyl cyclases containing 12 transmembrane-spanning regions and two cyclase domain. In Dictyostelium cells heterotrimeric G-proteins are essential for guanylyl cyclase activation by extracellular cAMP. In lysates, guanylyl cyclase activity is strongly stimulated by guanosine 5-3-O-(thio) triphosphate (GTP␥S), which is also a substrate of the enzyme. DdGCA was converted to an adenylyl cyclase by introducing three point mutations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…First, GTP␥S still stimulates GC activity in lysates from G␤-null cells (37), suggesting that at least the prevailing sGC is still sensitive to GTP␥S. In addition, upon mutation of GCA to an adenylyl cyclase, the enzyme is still stimulated by GTP␥S when expressed in cells with a deletion of G␤ or two G␣ subunits (34). Second, both GCA and sGC show normal Michaelis-Menten kinetics, suggesting that GTP does not stimulate these enzymes.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…First, GTP␥S still stimulates GC activity in lysates from G␤-null cells (37), suggesting that at least the prevailing sGC is still sensitive to GTP␥S. In addition, upon mutation of GCA to an adenylyl cyclase, the enzyme is still stimulated by GTP␥S when expressed in cells with a deletion of G␤ or two G␣ subunits (34). Second, both GCA and sGC show normal Michaelis-Menten kinetics, suggesting that GTP does not stimulate these enzymes.…”
Section: Discussionmentioning
confidence: 93%
“…1B), it would be interesting to determine the threedimensional structure of these unusual cyclases. Mutagenesis of GCA has shown that replacing the glutamate and histidine to the corresponding lysine and aspartate converts GCA into a fully active adenylyl cyclase (34). The notion that GCA and especially sGC contain many unusual amino acids at positions that have been shown to provide substrate specificity suggests that conversion of an adenylyl to a guanylyl cyclase can be achieved in different ways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed, that H504 serves as a hydrogen-bond donor to O 6 of the guanine moiety like the cysteine and serine in mammalian and Paramecium GCs, respectively. This is reasonable, because a change of glutamate-histidine to lysine-aspartate generated a functional AC, i.e., the unusual H504 is in the correct position for substrate-binding (17). In conclusion the GTP-selecting glutamate is functionally conserved among all class IIIaderived GCs investigated to date, but the second selector residue appears to be a variable H-bond donor or may be absent as in the case of Plasmodium GCs.…”
Section: Protozoan Gcs Derived From Class Iiiamentioning
confidence: 91%
“…Ras-interacting protein 3 (RIP3) is required for normal chemotaxis and for receptor activation of both ACA and GC (Lee et al 1999). Small G proteins have been implicated in the regulation of both the soluble and membrane-associated GCs of Dictyostelium (Roelofs et al 2001). In some respects, certain ras-null cells have chemotactic defects that are similar to that of G␣9 Q196L cells, suggesting a potential genetic or biochemical interaction (Wilkins and Insall 2001).…”
Section: Discussionmentioning
confidence: 99%